Sustainability and new information and comunication technologies - Tolón Becerra, Alfredo; Lastra Bravo, Xavier; Bienvenido Bárcena, Fernando; García Sobrino, Joaquín (M+A. Revista Electrónica de Medioambiente, 2012)
The field of sustainability has broadened its scope, incorporating social, economic and political aspects, from a first purely environmental dimension. The specialized knowledge, from multidisciplinary teams studies and general interest in environmental issues, is sometimes difficult to share due the different expression forms under field and the level of knowledge of the beneficiary. This problem is greater when trying to exchange this information through web pages. This paper shows how you can use a simple tool, the concept maps, to fix and exchange in a simple manner, yet powerful, this knowledge. We show the basics of concept maps and its application in the field of sustainability. Subsequently, we explain the process of website construction which contains the information previously gathered on sustainability indicators.
Keywords: Sustainability; Concept Maps; Sustainability indicators; Website